Yesus dan Hermeneutik Gezerah Shavah (Tinjauan Teks Kontroversi Sabat) - Tarigan, Wahyu Triwira; Bastanta, Dedi; Simanungkalit, Hulman (STT Injili Indonesia Medan, 2023)
Abstract: This article reviews the story of the Jesus controversy that occurred on the Sabbath in the synoptic gospel records (Mark 2:23-28; Matthew 12:1-8; Luke 6:1-5) in which the Pharisees encountered the actions that had been committed. by the disciples was a